Processing First-Year College Writing via Facebook Pedagogy in Linguistically and Culturally Diverse First-Year Composition Classes - Limbu, Marohang (Journal of International Students, 2011)
Facebook has a potential to critically engage students and merge their roles as writers and readers in a digital environment. Facebook reinforces students to share diverse cultural and individual rhetorical appeals, situations, and strategies. In this pedagogical setting, not only do students share a complex set of linguistic and cultural codes, but they also become technologically and cross-culturally competent human power. Facebook pedagogy encourages students to contest, question, and negotiate their cultural literacies and their prior experiences in first-year composition classes.